Can the Discovery Learning Model Increase Student Activity in Distance Learning? - Dita Salsavira Cahaya Ningrum; Pratiwi Pujiastuti; Asnafiyah; Gusti Izhar (Universitas Pendidikan Ganesha, 2022)
The implementation of online learning carried out in the past year has reduced student activity in learning so that many students are less focused in the learning process. This study aims to improve student learning activity in online learning using the Discovery Learning model. This study uses a collaborative classroom action research model of Kemmis and Mc Taggart. The research subjects were students of class B which consisted of 32 people. Data collection uses interview, observation, test, and documentation techniques as supporting data. Quantitative data were analyzed using descriptive statistics by looking for the mean. Qualitative data were analyzed using qualitative descriptive. The learning process is carried out online to increase student learning activity using the Discovery Learning model. The results showed that the use of this model in learning can improve the student learning process, especially in the online learning process. This is evidenced by the increase in learning activity which in the first cycle reached the classical percentage of 37.5% to 84.3% in the second cycle. This research implies that the Docovery Learning model can increase student activity in online learning in the Basic Social Studies course.